Analisis Kualitas Produk Toolbox Menggunakan Metode Seven Tools di PT. KSKB - Siti Khalimatul Inayah; Wahyudin Wahyudin; Dene Herwanto (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
The rapid development of the industrial world has made it a necessity for companies to compete with their competitors. Therefore, companies must control the quality of their products well, one of which is by analyzing defective products. The purpose of this research is to analyze the level of defects in Toolbox products produced by PT KSKB and provide improvement suggestions to reduce the level of defects in PT KSKB Toolbox products. This research uses data on the number of productions and the number of defective products obtained through field observations and interview processes. The method used in this research is the Seven Tools and Kaizen Five-M Checklist method of improvement analysis. Based on the data processing results, there are three types of defects in Toolbox products: burrs, materials with holes, and cutting with no precision. The most frequent type of defect is burrs (an uneven surface of the object due to the working process), with a value of 52.12%. Meanwhile, from the analysis of the Kaizen Five-M Checklist, periodic training (training and OJT) needs to be conducted for employees, routine machine maintenance needs to be carried out, standard operating procedures need to be evaluated, and work areas need to be evaluated to create a safe and comfortable working environment so that the level of product defects can be reduced.